The Long-Run Relationship between House Prices and Income in Malaysia - Ng, Edmund Hseen Long (2016)
In recent times, the growth rate of house prices has significantly outpaced income growth in Malaysia. Affordability of housing is now a major concern for many Malaysians especially the younger generation. This issue of house price outpacing income, however, is not unique to Malaysia as many countries have faced this issue. This has led to much empirical research done with regards to housing affordability. There are empirical researchers who argue that house prices must reflect its fundamentals in the long-run, meaning the gap between house price and income cannot keep growing larger and larger. Sooner or later prices must stagnate or fall for income to catch up. Using data from 1999 to 2015, I have tested this theory by employing two cointegration techniques. Testing the data using the traditional Engle & Granger test found no cointegrating relationship between house price and income. However, re-testing the data set with the more recently developed and more sophisticated bounds testing approach of Pesaran, Shin & Smith, I find empirical evidence that house price is cointegrated with income, construction cost and wealth. This implies that in the long-run, house prices in Malaysia must stagnate or fall to reflect its fundamentals more closely. However, there is no telling how long this might take especially if prices are currently not fundamentals-driven but are actually over-inflated due to the possibility of a housing market bubble. Thus in the short-run, many Malaysians will continue to suffer if the government does not take steps to alleviate the situation and possibly help restore this equilibrium relationship between house price and income that many researchers believe exists. Public policies such as macroprudential tools to curb speculation and over-investment should be imposed by the government so that prices are able to reflect its fundamental values more closely.